2020
DOI: 10.1590/fst.23019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical composition of germinated leguminous under abiotic stress conditions

Abstract: The aim of this study was to evaluate the impact of abiotic stress conditions on the synthesis of compounds with antioxidant properties in germinating seeds. The seeds of edible lentils (Lens culinaris L.), alfalfa (Medicago sativa L.), and mung beans (Vigna radiata L.) were germinated for 120 hours. We studied the influence of abiotic stress on the amount of dry matter, vitamin C and phenolic compounds, as well as flavonoids, in germinated seeds. The use of higher than optimal germination temperatures led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
(34 reference statements)
0
12
1
Order By: Relevance
“…It was observed that, after 24 h of germination, the TP for the Salcedo INIA variety had an increase of 61,3% and, 79,0% after 48 h. The Pasankalla variety increased to 55,2% and 110,7% after 24 and 48 h, respectively (Table 2). It could also be observed that Negra collana reported the highest increase (152,6% after 48 h), which is due to its genotypic differences; since this variety is darker, it releases a greater amount of phenolic compounds due to the leaching effect during germination (Televičiutė et al, 2020;Piñuel et al, 2019).…”
Section: Source: Authorsmentioning
confidence: 89%
See 4 more Smart Citations
“…It was observed that, after 24 h of germination, the TP for the Salcedo INIA variety had an increase of 61,3% and, 79,0% after 48 h. The Pasankalla variety increased to 55,2% and 110,7% after 24 and 48 h, respectively (Table 2). It could also be observed that Negra collana reported the highest increase (152,6% after 48 h), which is due to its genotypic differences; since this variety is darker, it releases a greater amount of phenolic compounds due to the leaching effect during germination (Televičiutė et al, 2020;Piñuel et al, 2019).…”
Section: Source: Authorsmentioning
confidence: 89%
“…During the germination process, the enzymatic systems are activated, mobilizing reserve proteins located in the cotyledons of the quinoa grain. In the same way, changes in the amino acid composition occur due to enzymatic activity (Gan et al, 2016;Televičiutė et al, 2020), which allows the production of peptides of intermediate molecular weight due biological activity (Torres, Cova, and Valera et al, 2018;Banchuen et al, 2009). This also happens with the mobilization of nitrogen stored in the quinoa grain, which allows a significant increase in protein, as observed by El-Safy, Mukhtar, and Salem (2013), Graf et al (2014), .…”
Section: Protein Contentmentioning
confidence: 99%
See 3 more Smart Citations